Hubungan Indeks Massa Tubuh (IMT) dan Lingkar Perut terhadap Risiko Jatuh Pada Lansia di Panti Jompo Werdha Lampung Selatan - M. Irfan zaki Rici; Dewi Nur Fiana; Anggraini Janar Wulan; Khairun Nisa Berawi (Majority, 2023)
Based on a survey in the United States, about 30% of the elderly population above 65 years fall each year. Falling is a direct impact of balance disorder. Factors related to falling incidence are body mass index (BMI) and abdominal circumference. This research aims to find the relationship between BMI and abdominal circumference on the risk of falling in elderly of Werdha Nursing House in South Lampung. This type of research is quantitative experimental with a cross-sectional design with 50 research subjects were selected using the total sampling technique. The research data were taken by measuring the abdominal circumference, BMI, and the Timed Up and Go Test. Data were processed using a computer program and analyzed by univariate and bivariate analysis using the Kruskal-walis test table b x k, with table 2 x 3 using the Kolmogorov-Smirnov test for 2 samples. The results were obtained by analyzing the primary data which resulted a univariate distribution of BMI with 26 normal respondents, 16 underweight respondents and 8 overweight respondents and normal abdominal circumference with 37 respondents and abnormal abdominal circumference with 13 respondents in Werdha Nursing House. Bivariate analysis resulted BMI (p value = 0,012) and circumference abdominal (p value = 0,000) with the risk of falling in elderly. This research shows that there is a relationship between BMI and abdominal circumference with the risk of falling in elderly of Werdha Nursing House South Lampung